The Influence of Motivational Climate Task-Oriented Against The Self-Discipline of Students in Physical Education - Priambodo, Anung (Universitas Negeri Semarang, 2017)
The purpose of this study was to determine: 1) The difference between the effects of training methods and the gradual striking distance striking distance remains as to the accuracy of hitting the ball Softball. 2) The difference in accuracy influence Softball hitting the ball between the athletes who have a good kinesthetic perception, kinesthetic perception was, and kinesthetic perception less. 3) The effect of interaction between training methods with kinesthetic perception as to the accuracy of hitting the ball Softball. This study used an experimental method with 2x3 factorial design. The results of this study were: 1) There is a significant difference between the gradual striking distance training methods and training methods remain striking distance of the ability to hit a softball with the result of the acquisition value p-value = 0.027 smaller than 0.05. 2) There is a significant difference between athletes who have a kinesthetic perception of good, moderate, lacking the ability to hit a softball with the result of the acquisition value p-value = 0.000, which is smaller than 0.05. 3) There is an interaction between striking distance training methods and kinesthetic perception of the ability to hit a softball with the result of the acquisition value p-value = 0.000, which is smaller than 0.05 The conclusion of this study were: 1) Gradually striking distance training methods have a better effect than the fixed striking distance training methods. 2) Athletes who have less kinesthetic perception has better results than the athletes who have good kinesthetic perception and being. 3) There is an interaction between striking distance training methods and kinesthetic perception of the ability to hit a softball.